Rhizobia increases the germination of Coffea arabica and Coffea canephora seeds. Second evidence in Cuba - Nápoles-Vinent, Sucleidi; Milanés-Riquene, Silfredo; Hernández-Forte, Ionel; Morales-Mena, Belkis; Nápoles-Garcias, María Caridad (Agronomía Mesoamericana, 2021)
Introduction. The slow and asynchronous germination of coffee seeds affects the obtaining of seedling and increases production costs. The application of plant growth promoting rhizobacteria (PGPRs) has shown to be an alternative to this problem. Objective. To evaluate the effect of rhizobia inoculation on the germination of two coffee cultivars under controlled and productive conditions. Materials and methods. During January and February 2020, two experiments were carried out at the Universidad de Oriente, Cuba, using ten rhizobia strains from legumes and grasses, and two coffee cultivars of economic importance in Cuba: Coffea arabica Isla 5-15 and Coffea canephora Pierre ex Froehner Robusta cultivars. The experiments were conducted, one under controlled conditions, where seed germination was evaluated in Petri dishes, and the other one using pre-germination beds. In both experiments, a completely randomized design was used and an analysis of variance was performed. Results. Under controlled conditions, the inoculation of strains Rpr11, Rpr2, 1-2, ICA8001, and Can3 increased germination percentage, germination energy, germination index, germination speed index, and vigor index. In the pre-germination beds, the inoculants based on the Rpr2 and Rpr11 strains produced the highest percentages of emergence and germination energy. Conclusion. The Rhizobium strains Rpr2 and Rpr11 increased seed germination of two varieties of coffee.